MAKNA PERANGKAT PEMUJAAN BUDHA PAKSA PAKARANA - Ida Bagus Purwa Sidemen (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
The Budha Paksa Pakarana has the means of worship as its must requirement possessed in performing its duties to lead and guide the Hindus in carrying out the ceremony. The means consists of rarapan, wanci kembang ura, wanci bhija, wanci samsam, wanci ghanda, pamandyangan, sesirat, pengasepan, pedamaran, patarana or lungka-lungka, saab/kereb/ hood, genta (genta padma), bajra, canting, and penastan. When a Pandita processing a ceremony, he is wearing attributes and clothing of Hindu high priest such as wastra, kampuh, kawaca, pepetet/ petet, santog, sinjang, slimpet/ sampet/ paragi, kekasang, astha bharana/ guduita, gondola, karna bharana, kanta bharana, rudrakacatan aksamala, gelangkana, angustha bharana, and an amakuta or the so-called bhawa or ketu. The results of observation and analysis show that the meaning of the Budha Paksa Pakarana a means of liaison between a pandita from the Buddhist group with Sang Hyang Buddha (God). The Panditas of the Buddha Paksa group have certain duties and obligations and agem-ageman to worship in a great ceremony of Hinduism in Bali. This typical Pandita performs worship for the middle realm (Bwah Loka), other than Pandita Shiva to worship for the upper realm (Swah Loka) and Pandita Bhujangga Waisnawa has the duty to perform worship for the underworld (Bhur Loka)